Moringa oleifera Lam. to accelerate wound healing: a review - Jaya, Fidi Bhawana; Syamsunarno, Mas Rizky Anggun Adipurna; Sahiratmadja, Edhyana (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2023)
An injury to the skin that disrupts the soft tissue may form a wound. The healing process in response to injury is a dynamic and well-regulated process of cellular, humoral, and molecular mechanisms that consists of four partly overlapping phases: hemostasis, inflammation, proliferation, and remodeling. An impaired wound-healing process may cause a formation of an abnormal scar and chronic wounds, leading to a reduced life quality. Therefore, it needs an optimal prevention strategy. Many modalities have been claimed to accelerate wound healing. The trend of using natural products is increasing in most Southeast Asian countries due to their biodiversity. Nowadays, studies on natural compounds are increasing to accelerate wound healing. Moringa oleifera Lam. is a high-value plant that each part of it has a high nutritional value as well as a great range of medicinal uses, including anti-inflammatory, antimicrobial, antioxidant, and wound healing properties. In this review, we have explored the M. oleifera that are very rich in vitamins, minerals, fatty acids, and phytochemical compounds like quercetin, kaempferol, and vicenin-2, that play a role in the wound healing process. Moreover, these compounds may enhance the healing of wounds with pathological conditions such as diabetes, immunocompromised and persistent infection.